Epidemiology of infective endocarditis: novel aspects in the twenty-first century. (2nd January 2022) - Arshad, Verda; Talha, Khawaja M.; Baddour, Larry M.
ABSTRACT: Introduction: The epidemiology of infective endocarditis (IE) in this millennium has changed with emergence of new risk factors and reemergence of others. This, coupled with modifications in national guidelines in the setting of a pandemic, prompted an address of the topic. Areas covered: Our goal is to provide a contemporary review of IE epidemiology considering changing incidence of rheumatic heart disease (RHD), cardiac device implantation, and injection drug use (IDU), with SARS-CoV-2 pandemic as the backdrop. Methods: PubMed and Google Scholar were used to identify studies of interest. Expert opinion: Our experience over the past two decades verifies the notion that there is not one 'textbook' profile of IE. Multiple factors have dramatically impacted IE epidemiology, and these factors differ, based, in part on geography. RHD has declined in many areas of the world, whereas implanted cardiovascular devices-related IE has grown exponentially. Perhaps the most influential, at least in areas of the United States, is injection drug use complicating the opioid epidemic. Healthy younger individuals contracting a potentially life-threatening infection has been tragic. In the past year, epidemiological changes due to the COVID-19 pandemic have also occurred. No doubt, changes will characterize IE in the future and serial review of the topic is warranted.